2021
DOI: 10.3390/gels7040234
|View full text |Cite
|
Sign up to set email alerts
|

A Short Review on the N,N-Dimethylacrylamide-Based Hydrogels

Abstract: Scientists have been encouraged to find different methods for removing harmful heavy metal ions and dyes from bodies of water. The adsorption technique offers promising outcomes for heavy metal ion removal and is simple to run on a large scale, making it appropriate for practical applications. Many adsorbent hydrogels have been developed and reported, comprising N,N-dimethylacrylamide (DMAA)-based hydrogels, which have attracted a lot of interest due to their reusability, simplicity of synthesis, and processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…49,50 In addition, hydrophobic interactions, hydrogen bonds and ionic dipole interactions in the N , N -dimethyl acrylamide structures can also enhance the mechanical strength of elastomers. 51 Considering the conductivity and other mechanical properties of PDES–DMA elastomers, we selected the PDES–DMA elastomer prepared with a molar ratio of PDES to DMA of 4 : 1 (toughness 55.5 MJ m −3 , Young's modulus 0.4 MPa) (Fig. 3c) for subsequent performance tests.…”
Section: Resultsmentioning
confidence: 99%
“…49,50 In addition, hydrophobic interactions, hydrogen bonds and ionic dipole interactions in the N , N -dimethyl acrylamide structures can also enhance the mechanical strength of elastomers. 51 Considering the conductivity and other mechanical properties of PDES–DMA elastomers, we selected the PDES–DMA elastomer prepared with a molar ratio of PDES to DMA of 4 : 1 (toughness 55.5 MJ m −3 , Young's modulus 0.4 MPa) (Fig. 3c) for subsequent performance tests.…”
Section: Resultsmentioning
confidence: 99%
“…It is found that the introduction of hydrolysis groups makes the polymer transform into polyelectrolyte, which is helpful to the extension of the molecular chain, and at the same time, it avoids a large amount of adsorption on the surface in the formation pores. The rheological properties of HPAM are greatly affected by the formation environment, so other synthetic polymers have also been applied to enhance oil recovery, including branched poly (propylene amide) [ 50 ], N, N-dimethylacrylamide copolymer [ 51 ], and HPAM derivatives with temperature and salt-resistant monomers (such as AMPS and NVP) [ 52 , 53 , 54 ]. No matter whether HPAM or other synthetic polymers, the polymer molecular chain has the characteristics of flexibility, easy change of molecular conformation, and extremely easy to bend and entangle.…”
Section: Why Choosing Supramolecular Polymer As the New Materials For...mentioning
confidence: 99%
“…The limitations demonstrated by BME matrices have led to the development of alternative 3D cell culture platforms, which aim to address these limitations. For example, hydrogels are water-swollen polymeric networks, formed through the interaction of hydrogel precursors, that can provide suitable environments for 3D cell culture [ 22 , 23 ]. Poly(ethylene)-glycol (PEG)-based hydrogels are synthetic 3D cell culture matrices, produced through crosslinking of PEG-based hydrogel precursors [ 16 , 21 , 24 , 25 ] that can be produced with high batch-to-batch reproducibility, therefore addressing the cross-batch variability observed in BME matrices.…”
Section: Introductionmentioning
confidence: 99%